Les blocs antiques en réemploi dans l’église Saint-André de Saint-Just-Saint-Rambert (Loire) - Jean-Claude Béal (Revue Archéologique du Centre de la France)
Antique architectural elements are used by the church-builder of the Middle Ages as building materials in Saint-André’s Church of Saint-Just-Saint-Rambert (Loire) for increase the prestige and the antiquity of the Saint-Rambert priory. Many of this spolia come from funeral monuments who could perhaps be linked with the villa of Saint-Côme, the most meridional of the Segusiave’s city, of which archaeological remains have been discovered 600 meters distance of Saint-André’s Church.